Low-molecular-weight composite anti-pollution agent for well cementation
By developing a low molecular weight composite anti-pollutant, the poor chemical compatibility problem of potassium polysulfonium water-based drilling fluid and cement slurry during the cementing process is solved, which significantly improves the compatibility between cement slurry and drilling fluid, extends the thickening time, suppresses adverse phenomena, and improves settlement stability.
Patent Information
- Application Number
- CN202510363693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The existing potassium polysulfonate water-based drilling fluid has poor chemical compatibility with cement slurry during cementing, which is prone to contact pollution, resulting in a shortening of the thickening time of cement slurry, and the occurrence of "core-encapsulated" and "bulging", affecting the cementing quality.
A low molecular weight composite anti-pollutant was developed. By stirring the low molecular weight phosphonic acid polymer solution and the silicate solution in a specific proportion, an anti-pollutant with strong adsorption and high temperature stability was prepared to reduce the pollution of the drilling fluid on the cement slurry.
It effectively improves the compatibility between cement slurry and drilling fluid, extends the thickening time of cement slurry, inhibits the "core-encapsulated" and "bulging", improves the settlement stability of water-based drilling fluid, and does not have a negative impact on the hydration of cement slurry.
Smart Images

Figure CN119875594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, in particular to a low molecular weight composite anti-pollution agent for cementing. Background Art
[0002] With the deepening of oil and gas well exploration and development, drilling operations face many challenges such as high temperature stability, reservoir protection and shale hydration. At present, among the water-based drilling fluid systems for deep and ultra-deep wells, KCl / polysulfone water-based drilling fluid has become an ideal choice due to its excellent performance in high temperature stability, anti-collapse inhibition and reservoir protection. Although KCl / polysulfone water-based drilling fluid has many advantages, it also has a serious engineering problem. After the drilling operation is completed, cement slurry cementing, as an indispensable part of the completion process, faces the problem of poor chemical compatibility between KCl / polysulfone water-based drilling fluid and cement slurry and easy contact contamination, which further affects the quality of cementing construction. Cementing construction is a systematic project with the characteristics of short construction time, strong technicality, many unknown factors and high risks. The quality of cementing not only directly affects whether the oil and gas well can be successfully completed, but also affects the service life and production of the oil and gas well. Therefore, ensuring the integrity of the cement ring to achieve well control safety, effectively isolate and support underground oil, gas and water layers is the core goal of cementing operations.
[0003] However, in actual cementing construction, the flushing efficiency of the isolation fluid and flushing fluid often cannot reach 100%, resulting in the inevitable contact and contamination of cement slurry and drilling mud residues. This contamination may cause complex situations in the cementing process due to factors such as drilling fluid compatibility, and even lead to the failure of cementing operations. Specifically, the cement slurry has problems such as "core encapsulation, bulging" and too short thickening time. In severe cases, it may also cause accidents such as blockage in the casing, annular bridge blockage, and inability to pull out the drill string or tubing after cementing, which is the so-called "sausage filling" and "flagpole insertion" phenomenon. These problems not only increase the difficulty and risk of construction, but may also have an adverse effect on the long-term stability and production efficiency of oil and gas wells. Therefore, how to effectively solve the problem of drilling fluid contamination of cement slurry during cementing and improve the integrity of the cement ring and cementing quality have become key technical problems that need to be solved in the current development of oil and gas wells.
[0004] The pollution mechanism behind it is mainly: (1) There are a large number of strong adsorption groups in the macromolecular polymers of drilling fluid treatment agents, such as carboxyl (-COOH), sulfonic acid (-SO 3 H) and amide groups (-CONH 2) etc. These strongly adsorbed groups undergo a deprotonation reaction under the strong alkaline conditions of cement slurry, resulting in very strong adsorption of these groups. At the same time, since the cement slurry system produces more metal ions during the hydration process and more active sites are exposed on the surface of cement particles, after the cement slurry system is mixed with the drilling fluid, the active strongly adsorbed groups in the polymer components of the drilling fluid will undergo adsorption reactions with the metal ions and cement particles, and gel structures will be generated between ions and particles, which will eventually lead to a serious decrease in the fluidity of the mixed slurry.
[0005] (2) The polymer molecules have strong adsorption properties and can bind to Ca 2+ A chelation reaction occurs to form a water-insoluble precipitate, which reduces the Ca content in the solution. 2+ The concentration cannot meet the hydration requirements, thus reducing the cement hydration process.
[0006] (3) When the sulfonated material treatment agent in the drilling fluid is exposed to a high temperature of about 120°C, it hydrolyzes to form a large number of carboxyl groups, which bridge with high-valent metal ions to form a network structure, and the viscosity of the system increases significantly. With the large-scale hydrolysis of the sulfonic acid groups, the viscosity increases further, and abnormal phenomena such as "bulging" and "core encapsulation" occur in the cement slurry.
[0007] At present, the most commonly used method is to increase the amount of spacer fluid and add a high amount of retarder or other acidic substances to the spacer fluid to prolong the thickening time of cement slurry contaminated by drilling fluid. However, this method does not fundamentally solve the pollution problem. In cementing operations, there is still contact pollution between cement slurry and drilling fluid. Secondly, the use of a large amount of spacer fluid and retarder means an increase in cost, which runs counter to the current environment of cost reduction and efficiency improvement. Therefore, it is very necessary to develop an efficient and convenient anti-pollution agent. Summary of the invention
[0008] In view of this, the present invention proposes a low molecular weight composite anti-pollution agent for cementing, which can effectively reduce the pollution of existing potassium polysulfonate water-based drilling fluid to cement slurry, improve the stability and fluidity of the mixed slurry, inhibit the phenomena of "coring" and "bulging", and significantly improve the sedimentation stability of water-based drilling fluid, and at the same time will not have a negative impact on the hydration of cement slurry.
[0009] The present invention discloses a low molecular weight composite anti-pollution agent for cementing, which is composed of the following components in parts by mass: Low molecular weight phosphonic acid polymer solution 60~85 Silicate solution 15~40; The preparation method comprises the following steps: stirring a low molecular weight phosphonic acid polymer solution and a silicate solution at a temperature not higher than 40° C. at a speed of 200-400 r / min until the mixture is uniform.
[0010] An embodiment of the present invention is that the silicate in the silicate solution is at least one of sodium silicate and potassium silicate, and the silicate modulus is 1.2-2.5.
[0011] One embodiment of the present invention is that the preparation method of the silicate solution comprises the following steps: stirring silicate powder in deionized water at a speed of 300-500 r / min at 40°C-70°C for at least 2 hours until uniform, to prepare a silicate solution with a mass fraction of 25%-45%.
[0012] One embodiment of the present invention is that the preparation method of the low molecular weight phosphonic acid polymer solution comprises the following steps: stirring the low molecular weight phosphonic acid polymer powder in deionized water at room temperature at a speed of 300-500 r / min for at least 2 hours until it is uniform, so as to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 35%-60%.
[0013] One embodiment of the present invention is that the method for preparing the low molecular weight phosphonic acid polymer comprises the following steps: Step S1: mixing a phosphonic acid group-containing monomer, a rigid group-containing monomer, and a carboxylic acid group-containing monomer in a molar ratio of 4-7:2-4:1-3 and dissolving them in deionized water to obtain a monomer solution with a mass fraction of 20%-50%; Step S2: adding a chain transfer agent accounting for 3% to 20% of the total weight of the monomer into the monomer solution and stirring and dissolving at a speed of 200 to 300 r / min, and heating to 45° C. under the protection of an inert gas during the stirring process; Step S3: adding a 10% to 20% initiator deionized water solution to the monomer solution with stirring, and the addition is completed within 30 min to 50 min, and then reacting at 50° C. to 70° C. for 3 h to 8 h, wherein the initiator in the initiator deionized water solution accounts for 0.05% to 1.5% of the total mass of the monomer; Step S4: distill the reactants under reduced pressure at 30° C. to 80° C., cool to room temperature, freeze, dry, and grind into powder.
[0014] Furthermore, the phosphonic acid group-containing monomer is one of vinyl phosphonic acid, dimethyl-vinyl phosphonate, diethyl-vinyl phosphonate and 2-acrylamide-2-methylpropanephosphonic acid.
[0015] Furthermore, the rigid group-containing monomer is one of N-vinyl pyrrolidone and 4-acryloylmorpholine.
[0016] Furthermore, the carboxylic acid group-containing monomer is one of acrylic acid, maleic acid, methacrylic acid and itaconic acid.
[0017] Furthermore, the chain transfer agent is a combination of one or more of mercaptoethanol, isopropanol, triethylamine, n-butanol, and sodium bisulfite.
[0018] Furthermore, the initiator is one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0019] The anti-pollution mechanism of the present invention can be found in Figure 6 As shown: low molecular weight phosphonic acid polymer, with a large number of strong adsorption groups of phosphonic acid, the adsorption strength is much greater than that of sulfonated treatment agents in potassium polysulfonate water-based drilling fluid. It shields metal ions and active sites in cement slurry by strongly adsorbing phosphonic acid groups, inhibits the reaction between drilling fluid treatment agents and cement slurry, and avoids the formation of agglomerated gel structure. Since the polymer in the anti-pollution agent is a low molecular weight multi-adsorption site polymer, it is largely only adsorbed on a single cement particle or forms a multi-dentate chelate with metal ions, reducing the possibility of cross-linking between cement particles and particles of the anti-pollution agent, inhibiting the generation of "core coating" in the polluted slurry, shortening the thickening time and excessive initial viscosity. The rigid groups improve the temperature resistance and structural stability of the anti-pollution agent at high temperatures. At the same time, the silicate in the anti-pollution agent can react with Ca in the cement slurry. 2+ The reaction produces a precipitate, which reduces the Ca content in the solution. 2+ concentration, inhibiting the large amount of adsorbent groups generated by the hydrolysis of sulfonic acid groups at high temperatures of 100°C to 130°C and Ca 2+ Reaction, inhibit the "bulging" phenomenon of polluted slurry, achieve the purpose of anti-pollution, at the same time, silicate reacts with Ca 2+ After the reaction produces calcium silicate, it also promotes the hydration process of cement slurry.
[0020] After the water-based drilling fluid is added to the present invention, it can simultaneously play a role in high-temperature suspension and stability of the slurry. The working principle is: the low molecular weight phosphonic acid polymer is adsorbed on the solid particles, and the carboxyl groups therein make the cement particles carry negative charges, thereby generating electrostatic repulsion between the solid particles and dispersing the solid particles.
[0021] The technical effects of the present invention are: (1) The present invention can form a stable slurry after being added into the drilling fluid or cement slurry system, which can meet the anti-pollution requirements under low addition conditions and can significantly reduce the amount of spacer fluid used.
[0022] (2) Compared with the traditional retarder anti-pollution agent that uses the retarding effect to prolong the thickening time, the present invention also has a very significant effect on inhibiting the "bulging" and "coring" phenomena and reducing the consistency of polluted slurry. The thickening time exceeds the thickening time of uncontaminated cement slurry, and the initial consistency is less than 30Bc.
[0023] (3) The present invention can be used for pollution control of conventional drilling fluid and cement slurry, and can also be used for cementing operations in complex formations such as high temperature, high pressure, and high salt.
[0024] (4) The present invention has a wide range of applications. While taking into account the function of an anti-pollution agent, it also has the function of a water-based drilling fluid suspending agent. After aging, the drilling fluid to which the present invention is added has a sedimentation stability that is significantly better than that of the drilling fluid without the addition.
[0025] (5) The low molecular weight phosphonic acid polymer in the present invention has a synergistic effect with silicate. Silicate can promote the hydration of cement. After the cement slurry, spacer fluid and water-based drilling fluid are mixed, the strength development of the mixed slurry is much stronger than that of the drilling fluid without adding anti-pollution agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a thickening test diagram of the cement system represented by Group 2 in Table 1 of the present invention; Figure 2 This is a thickening test diagram of the cement system represented by Group 8 in Table 1 of the present invention; Figure 3 This is a thickening test diagram of the cement system represented by Group 12 in Table 1 of the present invention; Figure 4 This is a thickening test diagram of the cement system represented by Group 14 in Table 1 of the present invention; Figure 5 This is a thickening test diagram of the cement system represented by Group 16 in Table 1 of the present invention; Figure 6 It is a schematic diagram of the anti-pollution principle of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used therein are all commercially available unless otherwise specified.
[0028] Example 1: 1. Preparation of low molecular weight phosphonic acid polymer (1) vinylphosphonic acid, N-vinyl pyrrolidone and itaconic acid were mixed in a molar ratio of 5:3:2 and dissolved in deionized water to prepare a monomer solution with a mass fraction of 20%; (2) Dissolve 20% of the total weight of the monomer in the isopropanol chain transfer agent in the monomer solution, put it into the reactor, stir and heat it to 45°C, control the stirring speed at 300r / min, and introduce inert gas nitrogen as a protective gas during the heating process; (3) Prepare a 10% mass concentration of initiator deionized water solution by adding 1% of the total mass of the monomer as ammonium persulfate initiator, and drip it into the monomer solution and stir evenly. The dripping rate of the initiator deionized water solution is controlled to be added within 30 minutes, and then the reaction temperature is controlled at 55°C and the reaction is carried out for 8 hours; (4) Using vacuum distillation to remove the chain transfer agent in the polymer solution, strictly controlling the heating temperature at 40°C ± 5°C until the fraction outflow rate slows down significantly and stops, cooling to room temperature, freeze drying, and grinding into powder to obtain a low molecular weight phosphonic acid polymer powder solid. The number average molecular weight of the polymer is 7310 as determined by gel permeation chromatography (GPC).
[0029] 2. Preparation of low molecular weight phosphonic acid polymer solution The obtained low molecular weight phosphonic acid polymer powder solid was dissolved in deionized water under stirring at room temperature, the stirring speed was controlled at 300 r / min, and the stirring was performed for 2 hours to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 50%.
[0030] 3. Preparation of silicate solution The low modulus sodium silicate powder with a modulus of 2.00 was stirred and dissolved in deionized water at 45°C. The stirring speed was controlled at 400 r / min and stirred for 2 hours to prepare a silicate solution with a mass fraction of 30%.
[0031] 4. Preparation of anti-pollution agent The low molecular weight phosphonic acid polymer solution and the silicate solution prepared above were stirred at a mass ratio of 70:30 at a speed of 200-400 r / min at 40° C. until they were uniform.
[0032] Example 2: 1. Preparation of low molecular weight phosphonic acid polymer (1) Dimethyl vinyl phosphonate, N-vinyl pyrrolidone and methacrylic acid were mixed in a molar ratio of 4:4:2 and dissolved in deionized water to prepare a monomer solution with a mass fraction of 20%; (2) 15% of the total weight of the monomer is dissolved in the monomer solution, and the mixture is placed in a reactor and heated to 45°C with stirring at a speed of 200 r / min. During the heating process, inert helium is introduced as a protective gas; (3) A 15% mass concentration of potassium persulfate initiator in deionized water solution was prepared by adding 1.5% of the total mass of the monomer into the initiator solution, and the solution was added dropwise into the monomer solution and stirred evenly. The dropping rate of the initiator solution was controlled to be completed within 40 min, and then the reaction temperature was controlled at 60 °C and the reaction was carried out for 6 h. (4) Using vacuum distillation to remove the chain transfer agent in the polymer solution, strictly controlling the heating temperature at 55°C ± 5°C until the fraction outflow rate slows down significantly and stops, cooling to room temperature, freeze drying, and grinding into powder to obtain a low molecular weight phosphonic acid polymer powder solid. The number average molecular weight of the polymer is 7284 as determined by gel permeation chromatography (GPC).
[0033] 2. Preparation of low molecular weight phosphonic acid polymer solution The obtained low molecular weight phosphonic acid polymer powder solid was dissolved in deionized water under stirring at room temperature, the stirring speed was controlled at 300 r / min, and the stirring was performed for 2 hours to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 35%.
[0034] 3. Preparation of silicate solution The low modulus sodium silicate powder with a modulus of 2.30 was stirred and dissolved in deionized water at 65°C. The stirring speed was controlled at 500 r / min and the stirring was performed for 2 hours to prepare a silicate solution with a mass fraction of 35%.
[0035] 4. Preparation of anti-pollution agent The low molecular weight phosphonic acid polymer solution and the silicate solution prepared above were stirred at a mass ratio of 80:20 at a speed of 200-400 r / min at 40° C. until they were uniform.
[0036] Example 3: 1. Preparation of low molecular weight phosphonic acid polymer (1) 2-acrylamide-2-methylpropanephosphonic acid, 4-acryloylmorpholine and maleic acid were mixed in a molar ratio of 6:2:2 and dissolved in deionized water to prepare a monomer solution with a mass fraction of 25%; (2) 10% of the total weight of the monomer is dissolved in the monomer solution, and the mixture is placed in a reactor and stirred and heated to 45°C. The stirring speed is controlled at 250 r / min, and inert helium is introduced as a protective gas during the heating process; (3) A potassium persulfate initiator with a mass concentration of 10% was prepared by adding 0.5% of the total weight of the monomer into a deionized water solution of the initiator, and the solution was dropped into the monomer solution and stirred evenly. The dropping rate of the deionized water solution of the initiator was controlled to be added within 50 minutes, and then the reaction temperature was controlled at 55°C and the reaction was carried out for 7 hours; (4) Using vacuum distillation to remove the chain transfer agent in the polymer solution, strictly controlling the heating temperature at 50°C ± 5°C until the fraction outflow rate slows down significantly and stops, cooling to room temperature, freeze drying, and grinding into powder to obtain a low molecular weight phosphonic acid polymer powder solid. The number average molecular weight of the polymer is 2836 as determined by gel permeation chromatography (GPC).
[0037] 2. Preparation of low molecular weight phosphonic acid polymer solution The obtained low molecular weight phosphonic acid polymer powder solid was stirred and dissolved in deionized water at room temperature, the stirring speed was controlled at 300 r / min, and the stirring was performed for 2 hours to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 40%.
[0038] 3. Preparation of silicate solution The low modulus sodium silicate powder with a modulus of 2.35 was stirred and dissolved in deionized water at 60°C, the stirring speed was controlled at 400 r / min, and the stirring was performed for 2 hours to prepare a silicate solution with a mass fraction of 30%.
[0039] 4. Preparation of anti-pollution agent The low molecular weight phosphonic acid polymer solution and the silicate solution prepared above were stirred at a mass ratio of 85:15 at a speed of 200-400 r / min at 40° C. until they were uniform.
[0040] Example 4: 1. Preparation of low molecular weight phosphonic acid polymer (1) diethyl vinyl phosphonate, 4-acryloylmorpholine and acrylic acid were mixed in a molar ratio of 6.5:2.5:1 and dissolved in deionized water to prepare a monomer solution with a mass fraction of 30%; (2) Dissolve 15% of the total weight of the monomer in the monomer solution, add the triethylamine chain transfer agent into the reactor, stir and heat to 45°C, control the stirring speed at 300 r / min, and introduce inert gas nitrogen as a protective gas during the heating process; (3) Prepare a 15% mass concentration of ammonium persulfate initiator in a deionized water solution with a concentration of 15% by mass, and drip it into the monomer solution and stir evenly. The dripping rate of the deionized water solution is controlled to be added within 30 minutes, and then the reaction temperature is controlled at 65°C and the reaction is carried out for 4 hours; (4) Using vacuum distillation to remove the chain transfer agent in the polymer solution, strictly controlling the heating temperature at 45°C ± 5°C until the fraction outflow rate slows down significantly and stops, cooling to room temperature, freeze drying, and grinding into powder to obtain a low molecular weight phosphonic acid polymer powder solid. The number average molecular weight of the polymer is 8434 as determined by gel permeation chromatography (GPC).
[0041] 2. Preparation of low molecular weight phosphonic acid polymer solution The obtained low molecular weight phosphonic acid polymer powder solid was stirred and dissolved in deionized water at room temperature, the stirring speed was controlled at 300 r / min, and the stirring was performed for 2 hours to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 40%.
[0042] 3. Preparation of silicate solution The low modulus sodium silicate powder with a modulus of 2.50 was stirred and dissolved in deionized water at 70°C, the stirring speed was controlled at 450 r / min, and the stirring was performed for 2 hours to prepare a silicate solution with a mass fraction of 30%.
[0043] 4. Preparation of anti-pollution agent The low molecular weight phosphonic acid polymer solution and the silicate solution prepared above were stirred at a mass ratio of 60:40 at a speed of 200-400 r / min at 40° C. until they were uniform.
[0044] Comparative Example 1 The raw material dosage and implementation method of Comparative Example 1 are basically the same as those of Example 1, except that no chain transfer agent is added in Comparative Example 1, and the molecular weight of the phosphonic acid-based polymer finally obtained is 110991.
[0045] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no silicate solution is prepared, the anti-pollution agent is only composed of a low molecular weight phosphonic acid-based polymer solution, and the amounts of other raw materials and the implementation methods are the same.
[0046] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no low molecular weight phosphonic acid-based polymer solution is prepared, the anti-pollution agent is only composed of a silicate solution, and the amounts of other raw materials and the implementation methods are the same.
[0047] Comparative Example 4 Comparative Example 4 is a commercial retarder BCR-300L.
[0048] In order to better illustrate the technical effects of the present invention, corresponding characterization and performance evaluation are provided for relevant embodiments below.
[0049] 1. Evaluation of anti-pollution performance Table 1 Anti-pollution performance evaluation results
[0050] As shown in Table 1, after adding potassium polysulfone water-based drilling fluid to the product of the present invention, the compatibility of cement slurry and drilling fluid is significantly improved, the fluidity and compressive strength of the slurry are improved, the thickening time is prolonged, and the "core" and "bulging" problems of the slurry are effectively suppressed.
[0051] Figure 1 It represents the cement system of Group 2 cement slurry and drilling fluid in a ratio of 7:3 in Table 1. Figure 2 It represents the cement slurry of Group 8 in Table 1 and the mixed cement system of drilling fluid in a ratio of 7:3. Figure 1 and Figure 2By comparison, it can be found that the system of Group 2 without adding anti-pollution agent has a thickening time of only 68 minutes, and is accompanied by problems such as "core encapsulation" and "bulging". The cement slurry with a larger molecular weight polymer-silicate composite anti-pollution agent in Comparative Example 1 and a 7:3 mixing cement system of drilling fluid, i.e. Group 12 in Table 1, has the following results: Figure 3 As shown, it can be seen that the "core encapsulation" phenomenon has not been effectively suppressed. The initial viscosity of the slurry exceeds 35Bc, and after the temperature rises to nearly 120°C, it thickens abnormally, and the viscosity rises to nearly 50Bc. This may be due to the fact that the larger molecular weight of the strongly adsorbed polymer forms a stronger cross-linking structure between cement particles, and together with the polymer treatment agent in the drilling fluid, it promotes the thickening of the slurry, proving that controlling the molecular weight of the anti-pollution agent is one of the key factors to ensure its normal effect in the cement system.
[0052] The thickening test results of group 14 in Table 1 are as follows Figure 4 As shown by Figure 4 It can be seen that after adding the anti-pollution agent composed of a single low molecular weight phosphonic acid polymer in Comparative Example 2 to the mixed cement system of cement slurry and drilling fluid in a ratio of 7:3, the "bulging" phenomenon cannot be effectively suppressed; and according to the ratio of Group 16 in Table 1, after adding the anti-pollution agent composed of a single silicate in Comparative Example 3 to the mixed system of cement slurry and drilling fluid in a ratio of 7:3, the results are as follows Figure 5 As shown, the "core coating" phenomenon and shortened thickening time also appeared. At the same time, combined with the performance of the commercial anti-pollution agent BCR-300L in the system in Comparative Example 4, even when the thickening time requirement is met and the amount added reaches 10wt%, the compressive strength of the slurry after curing after mixing still shows extremely low characteristics. It can be seen that the anti-pollution agent of the present invention can show good comprehensive performance under the premise that the amount added is much lower than the amount of the retarder in Comparative Example 4. This is mainly due to the synergistic effect of the low molecular weight phosphonic acid polymer-silicate in the present invention, which competes with the drilling fluid treatment agent for adsorption, and can effectively reduce the metal ion concentration of cement slurry in the mixed slurry solution after contact, and shield the active sites of cement particles, inhibit the pollution of cement slurry by strong adsorption treatment agents, and achieve the purpose of anti-pollution. Due to the presence of silicate, under the premise of achieving anti-pollution, it will not have a negative impact on the normal hydration reaction of cement slurry, and has a promoting effect on the hydration degree of cement slurry after pollution.
[0053] 2. Suspension performance evaluation According to the national standard GB / T 16783.1-2014 test method, 2.20g / cm 3Drilling fluid stability test. The amount of anti-pollution agent added is 1.5wt% of the total volume of the drilling fluid. After the drilling fluid is stirred and sealed for 24 hours, it is placed in a high-temperature aging tank after stirring for 20 minutes. After hot rolling aging at 200°C for 16 hours, it is stirred for 20 minutes and left to stand for 4 hours. The density difference between the upper and lower suspensions is measured. At the same time, a blank group 4 without adding anti-pollution agent is set as a control. The test results are shown in Table 2: Table 2 Suspension performance evaluation results
[0054] From the results in Table 2, it can be seen that the water-based drilling fluid added in the present invention still exhibits good sedimentation stability after aging at a high temperature of 200°C for 16 hours, which proves that the present invention can effectively improve the chemical compatibility between cement slurry, spacer fluid and drilling fluid, reduce the risk of weighting agent sedimentation, annulus blockage and pump blocking during cementing, and ensure the safety of cementing construction and cementing quality.
[0055] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A low molecular weight composite anti-pollution agent for cementing, characterized in that: The composition is as follows in parts by mass: Low molecular weight phosphonic acid polymer solution 60~85 Silicate solution 15~40; The preparation method comprises the following steps: stirring a low molecular weight phosphonic acid polymer solution and a silicate solution at a temperature not higher than 40° C. at a speed of 200-400 r / min until the mixture is uniform.
2. The low molecular weight composite anti-pollution agent for cementing according to claim 1, characterized in that: The silicate in the silicate solution is one of sodium silicate and potassium silicate, and the silicate modulus is 1.2-2.
5.
3. The low molecular weight composite anti-pollution agent for cementing according to claim 1, characterized in that: The preparation method of the silicate solution comprises the following steps: stirring silicate powder in deionized water at 40° C. to 70° C. at a speed of 300 to 500 r / min for at least 2 hours until it is uniform, so as to prepare a silicate solution with a mass fraction of 25% to 45%.
4. The low molecular weight composite anti-pollution agent for cementing according to claim 1, characterized in that: The preparation method of the low molecular weight phosphonic acid polymer solution comprises the following steps: stirring the low molecular weight phosphonic acid polymer powder in deionized water at room temperature at a speed of 300-500 r / min for at least 2 hours until it is uniform, so as to prepare a low molecular weight phosphonic acid polymer solution with a mass fraction of 35%-60%.
5. The low molecular weight composite anti-pollution agent for cementing according to claim 1, characterized in that: The preparation method of the low molecular weight phosphonic acid polymer comprises the following steps: Step S1: mixing a phosphonic acid group-containing monomer, a rigid group-containing monomer, and a carboxylic acid group-containing monomer in a molar ratio of 4-7:2-4:1-3 and dissolving them in deionized water to obtain a monomer solution with a mass fraction of 20%-50%; Step S2: adding a chain transfer agent accounting for 3% to 20% of the total weight of the monomer into the monomer solution and stirring and dissolving at a speed of 200 to 300 r / min, and heating to 45° C. under the protection of an inert gas during the stirring process; Step S3: adding a 10% to 20% initiator deionized water solution to the monomer solution with stirring, and the addition is completed within 30 min to 50 min, and then reacting at 50° C. to 70° C. for 3 h to 8 h, wherein the initiator in the initiator deionized water solution accounts for 0.05% to 1.5% of the total mass of the monomer; Step S4: distill the reactants under reduced pressure at 30° C. to 80° C., cool to room temperature, freeze, dry, and grind into powder.
6. The low molecular weight composite anti-pollution agent for cementing according to claim 5, characterized in that: The phosphonic acid group-containing monomer is at least one of vinyl phosphonic acid, dimethyl-vinyl phosphonate, diethyl-vinyl phosphonate and 2-acrylamide-2-methylpropanephosphonic acid.
7. The low molecular weight composite anti-pollution agent for cementing according to claim 5, characterized in that: The rigid group-containing monomer is one of N-vinyl pyrrolidone and 4-acryloylmorpholine.
8. The low molecular weight composite anti-pollution agent for cementing according to claim 5, characterized in that: The carboxylic acid group-containing monomer is one of acrylic acid, maleic acid, methacrylic acid and itaconic acid.
9. The low molecular weight composite anti-pollution agent for cementing according to claim 5, characterized in that: The chain transfer agent is a combination of one or more of mercaptoethanol, isopropanol, triethylamine, n-butanol, and sodium bisulfite.
10. The low molecular weight composite anti-pollution agent for cementing according to claim 5, characterized in that: The initiator is one of ammonium persulfate, sodium persulfate and potassium persulfate.
Citation Information
Patent Citations
Phosphonic acid group-containing polymer drilling fluid viscosity reducer and preparation method thereof
CN102899006A
Oil well cement anti-pollution agent
CN109097012A
High temperature resistant organic phosphonic acid polymer fluid loss agent, and preparation method and applications thereof
CN109851710A
Organic phosphonic acid polymer fluid loss agent, and preparation method and applications thereof
CN109852352A
Ultrahigh-temperature large-temperature-difference retarder for oil well cement and preparation method thereof
CN117384326A
Cited By
Composite grinding aid for quartz ore grinding and preparation method thereof
CN121991299A